PENGARUH MEDIA TRIP BOX DALAM MENGENALKAN KOSAKATA TRANSPORTASI BAHASA INGGRIS PADA ANAK USIA 4-5 TAHUN DI TAMAN KANAK-KANAK PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - Negsa Martoni; Elise Muryanti; Asdi Wirman; Saridewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Introducing English during early childhood is an important effort to develop children's language skills during the golden age period. However, English learning in kindergarten still faces several challenges, particularly the limited use of attractive learning media, resulting in children's vocabulary development not being optimal. This study aimed to determine the effect of Trip Box media on introducing English transportation vocabulary to children aged 4-5 years at Taman Kanak-kanak Pembangunan Laboratorium Universitas Negeri Padang. This research employed a quantitative approach using a quasi-experimental method. The population consisted of all children aged 4-5 years, while the sample included Class B4 as the experimental group and Class B3 as the control group, each consisting of 15 children selected through purposive sampling. Data were collected through observation and performance tests and analyzed using normality, homogeneity, and independent sample t-tests with SPSS version 25. The findings revealed that the post-test mean score of the experimental class (21.2) was higher than that of the control class (19.8). The hypothesis test showed a significance value (2-tailed) of 0.008 (<0.05), indicating that Trip Box media significantly influenced children's English transportation vocabulary acquisition. Therefore, Trip Box can be recommended as an effective, interactive, and enjoyable learning medium for introducing English vocabulary to early childhood learners.